MicroRNAs: from female fertility, germ cells, and stem cells to cancer in humans - Virant-Klun, Irma; Ståhlberg, Anders; Kubista, Mikael; Skutella, Thomas (Stem cells international, 2016)
MicroRNAs are a family of naturally occurring small noncoding RNA molecules that play an important regulatory role in gene expression. They are suggested to regulate a large proportion of protein encoding genes by mediating the translational suppression and posttranscriptional control of gene expression. Recent findings show that microRNAs are emerging as important regulators of cellular differentiation and dedifferentiation, and are deeply involved in developmental processes including human preimplantation development. They keep a balance between pluripotency and differentiation in the embryo and embryonic stem cells. Moreover, it became evident that dysregulation of microRNA expression may play a fundamental role in progression and dissemination of different cancers including ovarian cancer. The interest is still increased by the discovery of exosomes, that is, cell-derived vesicles, which can carry different proteins but also microRNAs between different cells and are involved in cell-to-cell communication. MicroRNAs, together with exosomes, have a great potential to be used for prognosis, therapy, and biomarkers of different diseases including infertility. The aim of this review paper is to summarize the existent knowledge on microRNAs related to female fertility and cancer: from primordial germ cells and ovarian function, germinal stem cells, oocytes, and embryos to embryonic stem cells.